2009
DOI: 10.1108/13673270910988178
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the digital divide: policy analysis for knowledge societies

Abstract: PurposeThe purpose of this paper is to report the results of using the framework in the field for the purpose of formulating knowledge policies. The framework derives from a conceptual model for analyzing knowledge development overviewed by the authors in a previous paper.Design/methodology/approachThe paper uses the conceptual framework of 13 dimensions for knowledge policy‐making analysis and qualitative focus group discussions by means of what is known as a knowledge SWOT analysis. Such an exercise ordinari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 25 publications
0
33
0
1
Order By: Relevance
“…Folorunso et al [7] and [14] found that mass unawareness, low computer literacy level and cost were identified as critical factors affecting the acceptability of e-learning by students and lecturers of Nigerian universities. Sharma et al [15] points out that e-learning places high demand on learners who have to be more proactive and disciplined than in traditional face-to-face education. Schulmeister [17] states that experience proved that the benefits of e-learning could not be fully taken advantage of, expectations could not be met and that technology often was used to simply reinforce outmoded approaches to learning.…”
Section: Challenges Of E-learning In Nigerian University Educationmentioning
confidence: 99%
“…Folorunso et al [7] and [14] found that mass unawareness, low computer literacy level and cost were identified as critical factors affecting the acceptability of e-learning by students and lecturers of Nigerian universities. Sharma et al [15] points out that e-learning places high demand on learners who have to be more proactive and disciplined than in traditional face-to-face education. Schulmeister [17] states that experience proved that the benefits of e-learning could not be fully taken advantage of, expectations could not be met and that technology often was used to simply reinforce outmoded approaches to learning.…”
Section: Challenges Of E-learning In Nigerian University Educationmentioning
confidence: 99%
“…New technological advances have contributed to the fact that research methodologies based on bibliographic consultation, as well as on maps and cartography, official archives, etc., are evolving towards a more streamlined system based on computer advances and data availability. This progression allows us to delve into the different dimensions of the information, establishing, for example, relationships or patterns that would otherwise be very difficult to identify [13,41,42].…”
Section: Mapping Of Natural Cultural and Human Resources Consensus mentioning
confidence: 99%
“…The recognition of cities as an important frontier for addressing human development challenges and their key roles as macro-economic engines has stimulated interest amongst practitioners and theoreticians in the role of knowledgebased development in the urban environment (Borja and Castells, 1997;Bounfour and Edvinsson 2005;Carrillo, 2004Carrillo, , 2015Florida, 2004;Sharma et al, 2008Sharma et al, , 2009. This in turn has given rise to an area of specialization known as knowledge-based urban development or knowledge cities, which is a new hybrid of knowledge-based development and urban studies and which seeks to provide strategic responses for addressing the complex multidisciplinary challenges that cities face (Carrillo, 2004(Carrillo, , 2015.…”
Section: The Intersection Of Knowledge and Citiesmentioning
confidence: 99%